Combined epitaxial self-assembly of block copolymer lamellae on a hexagonal pre-pattern within microgrooves1. Issue 21 (7th June 2015) - Jung, Hyunjung; Woo, Sanghoon; Park, Sungmin; Lee, Sumi; Kang, Minhyuk; Choe, Youngson; Son, Jeong Gon; Ryu, Du Yeol; Huh, June; Bang, Joona
<x xml:space="preserve">Abstract</x> We demonstrated a simple and feasible technology for a DSA process by combining graphoepitaxy with "inexpensive" chemoepitaxial assembly to improve the alignment of lamellar microdomains.